2011
DOI: 10.1111/j.1365-263x.2011.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal development of the mandibular permanent first molar in infants with isolated cleft palate

Abstract: Children with ICP showed smaller dimensions of the M1(inf) , and in addition, the maturation of M1(inf) was delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…In the present study, like in the study by Hermann et al, lateral cephalograms were used to assess tooth maturation of the of M1 inf according to Haavikko, which may introduce a possible error in case of asymmetric dental development. However, previous studies have shown that asymmetric dental development is most likely in the region in close proximity to the cleft (eg, maxillary incisors), whereas an asymmetric development of the posterior teeth is rare …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the present study, like in the study by Hermann et al, lateral cephalograms were used to assess tooth maturation of the of M1 inf according to Haavikko, which may introduce a possible error in case of asymmetric dental development. However, previous studies have shown that asymmetric dental development is most likely in the region in close proximity to the cleft (eg, maxillary incisors), whereas an asymmetric development of the posterior teeth is rare …”
Section: Discussionmentioning
confidence: 96%
“…[20][21][22][23] Delay in mineralization of M1 inf was also found in a previous study by us on infants and young children with CP. 24 The delayed mineralization of the teeth observed in subjects with cleft palate with/without a cleft lip might be related to the observed delay in somatic development (first seen as reduced body weight and later as reduced body length). 24 The delay in somatic development as well as the delay in mineralization of the teeth is most likely caused by the feeding difficulties in cleft infants 25,26 and subsequent malnutrition/undernourishment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations